Technological Innovation Improves SMEs Performance Through Knowledge Management Practices - Rahmawati Rahmawati; Andi Aris Mattunruang; Yonas Ferdinand Riwu (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines how technological innovation influences the performance of SMEs in South Sulawesi through the role of knowledge management. The topic is important as many SMEs are transitioning from traditional business practices to digital platforms, particularly e-commerce, supported by increasing government initiatives. Understanding this transformation provides insights into improving competitiveness and sustainability in emerging markets. Design/methodology/approach – This research employs a quantitative approach using survey data collected from SMEs in South Sulawesi. The study integrates the technology acceptance model to analyze the relationship between innovation, trust, and interest in e-commerce adoption. Data were analyzed using least squares regression to measure the effect of technological innovation on SME performance, with knowledge management as a supporting construct. Finding/Results – The results indicate that SMEs adopting technological innovation demonstrate significantly better performance compared to those that rely on traditional methods. Innovation, supported by effective knowledge management practices, enhances productivity and competitiveness. Originality/Value – This study highlights the strategic role of integrating technological innovation and knowledge management in improving SME performance, offering practical implications for policymakers and business actors in accelerating digital transformation.